Development of Green Resin Using Solid Waste Protein Soybean Curd “Tofu” Production - Sujito Sujito (Journal of Tropical Life Science, 2010)
One of the most concerns associated with many commercially available composites is that they used of non-degradable resins and fibers that primarily made using non-degradable, petroleum-based chemicals as feed stock. These conditions will create a serious problem in term of waste disposal after end of their life. Unlike petroleum, plant based protein and starches are yearly renewable. These resins are increasingly developed for various applications as replacements for non-degradable petroleum based resins. In addition, these resins may be easily composted after their life. In this study, Soybean Pulp Hemi-cellulose (SPH) was modified by cross-linking it with glutaraldehyde (GA). The modified SPH resins were characterized for its surface morphology, tensile and mass losses or biodegradability properties. The effect of GA on the surface morphology, tensile and biodegradability of the SPH resins were discussed. The SPH resins showed improved surface morphology and ductility. However, the increasing the GA content reduces the Young's modulus of the SPH resins. The SPH resins exhibited fracture stress point and Young's modulus maximum of and 3.02 MN/m2, respectively, and biodegradability of 40.42% after 30 days placed on the open air. These properties seem to be sufficient for developing green composites from the SPH resins reinforced with natural fiber for indoor structural applications. Keywords: Green Resin, Soybean Pulp Hemi-cellulose (SPH), Mechanical Properties, Biodegradation.